Adult growth hormone deficiency: Optimizing transition of care from pediatric to adult services. (February 2021) - Yuen, Kevin C.J.; Alter, Craig A.; Miller, Bradley S.; Gannon, Anthony W.; Tritos, Nicholas A.; Samson, Susan L.; Dobri, Georgiana; Kurtz, Kristine; Strobl, Frank; Kelepouris, Nicky
Abstract: Objective: Most patients with childhood-onset growth hormone deficiency (CO-GHD) receive treatment with exogenous growth hormone (GH) to facilitate the attainment of their full potential adult height. Recent evidence suggests that continuing GH administration during the transition period between the end of linear growth and full adult maturity is necessary for proper body composition and bone and muscle health, and may also have beneficial effects on metabolic parameters, bone mineral density, and quality of life. The timing of this transition period coincides with the transfer of care from a pediatric to an adult endocrinologist, creating the potential for a care gap as a consequence of losing the patient to follow-up. Design: An advisory board comprising both pediatric and adult endocrinologists was assembled to address current clinical unmet needs and to collaborate on a structured transitional plan for optimal management of patients with CO-GHD. Insights/conclusion: The advisors suggest collaborative, multidisciplinary approaches to ensure continuity of care; ongoing testing and monitoring of GHD status into adulthood; and a clearly structured protocol that includes practical guidance for clinicians to establish best practices for transitioning older adolescents with persistent CO-GHD to adult care. Highlights: Effective transition of care from pediatric to adult services is challenging. Patients transitioning from childhood to adulthood often experience a care gap. Endocrinologists met and discussed unmet needs and optimal management of patients. Collaborative, multidisciplinary approaches to ensure continuity of care are needed. A consensus document providing practical guidance on transition care is needed.